Method for treating a zeolite membrane

CN122995898APending Publication Date: 2026-10-27NGK CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202580018948.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-18
Filing Date
2025-02-18
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

因此,若将沸石膜复合体直接保管,则发生朝向沸石膜的进一步的水分子吸附及吸附于沸石膜的水分子的脱离等,在以相同条件制作的多个沸石膜复合体中,沸石膜的透过性能(例如分离性能、透过速度)有可能产生偏差

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122995898A_ABST
    Figure CN122995898A_ABST
Patent Text Reader

Abstract

The treatment method of the zeolite membrane includes the following steps: preparing a zeolite membrane subjected to a heat treatment (step S31); after step S31, bringing a moisture-containing gas having a volume moisture rate of 4000 ppmv or more and 65000 ppmv or less into contact with the zeolite membrane, thereby causing water molecules to be adsorbed to the zeolite membrane (step S32); and after step S32, partially removing the water molecules adsorbed to the zeolite membrane (step S33). Accordingly, the permeation performance of the zeolite membrane can be stabilized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for treating zeolite membranes.

[0002] [Reference to relevant applications]

[0003] This application claims priority to Japanese Patent Application JP2024-41921, filed on March 18, 2024, the entire disclosure of which is incorporated herein by reference. Background Technology

[0004] Currently, various studies and developments are underway regarding the separation of specific molecules using separation membranes such as zeolite membranes. For example, a known technique involves supplying a mixed gas containing multiple gases to a zeolite membrane, allowing highly permeable gases to pass through the membrane's pores, thereby separating them from the mixed gas. Additionally, a known technique involves subjecting the zeolite membrane to specific treatments, thereby improving its performance.

[0005] For example, Japanese Patent Application Publication No. 2013-013884 (Document 1) proposes a treatment method whereby the zeolite membrane composite is heated at a temperature of 50°C or higher, and then immersed in water at a temperature of 40°C or higher but below 300°C for at least one hour (hereinafter referred to as "hot water treatment"). Document 1 states that through this hot water treatment, the Si-O-Si bonds formed on the zeolite surface due to sintering, etc., are transformed into highly hydrophilic Si-OH bonds, thus improving water permeability. Furthermore, Document 1 also states that through this hot water treatment, the fine defects in the zeolite membrane are repaired using amorphous silica or similar materials within the defects, thus improving the performance of the zeolite membrane.

[0006] Japanese Patent Application Publication No. 2016-159185 (Document 2) proposes a technique of treating a zeolite membrane composite in a solvent under a pressure of 0.5 MPa or higher. Document 2 states that this treatment causes certain substances in the solvent to enter defects in the zeolite membrane, thereby sealing the defects and improving separation performance.

[0007] However, in the manufacture of zeolite membrane composites, the zeolite membrane is typically sintered at high temperatures to remove impurities and organic structure-directing agents. Water molecules in the atmosphere readily adsorb onto zeolite membranes sintered at such high temperatures. Therefore, if the zeolite membrane composite is stored directly, further adsorption of water molecules towards the zeolite membrane and detachment of adsorbed water molecules occur. This can lead to variations in the permeation performance (e.g., separation performance, permeation rate) among multiple zeolite membrane composites manufactured under the same conditions. Furthermore, even for the same zeolite membrane composite, changes in storage conditions can cause variations in permeation performance.

[0008] However, although research on improving the performance of zeolite membranes is underway, as in References 1 and 2, techniques for suppressing deviations in the permeation performance of zeolite membranes (i.e., stabilizing the permeation performance of zeolite membranes) have not been explored. Summary of the Invention

[0009] This invention relates to a method for treating zeolite membranes, the purpose of which is to stabilize the permeation performance of zeolite membranes.

[0010] The invention of Scheme 1 is a method for treating a zeolite membrane, comprising the following steps: a) preparing a heat-treated zeolite membrane; b) after step a), contacting a moisture-containing gas with a volume water content of 4000 ppmv or more and 65000 ppmv or less with the zeolite membrane, thereby adsorbing water molecules onto the zeolite membrane; and c) after step b), partially removing the water molecules adsorbed onto the zeolite membrane.

[0011] According to the present invention, the permeation performance of zeolite membranes can be stabilized.

[0012] The invention of Scheme 2 is based on the zeolite membrane treatment method of Scheme 1. In step c), water molecules adsorbed on the zeolite membrane are partially removed by performing any one or more of the following treatments: depressurization treatment of the zeolite membrane, treatment of replacing the atmosphere around the zeolite membrane with a dry gas with a water volume fraction lower than that of the water-containing gas, treatment of blowing the dry gas onto the zeolite membrane, and treatment of storing the zeolite membrane and the water adsorption material together in a container.

[0013] The invention of Scheme 3 is based on the zeolite membrane treatment method of Scheme 2. In step c), a depressurization treatment is performed on the zeolite membrane. In the depressurization treatment, the zeolite membrane is kept in a vacuum atmosphere for more than 3 hours and less than 240 hours.

[0014] The invention of Scheme 4 is based on the zeolite membrane treatment method of any one of Schemes 1 to 3, wherein the moisture-containing gas is atmospheric gas.

[0015] The invention of Scheme 5 is based on the zeolite membrane treatment method of Scheme 4. In step b), the atmosphere with a relative humidity of 25% or more and 80% or less is brought into contact with the zeolite membrane for more than 1 hour and less than 72 hours, thereby causing water molecules to be adsorbed onto the zeolite membrane.

[0016] The invention of Scheme 6 is based on the zeolite membrane processing method of any one of Schemes 1 to 3 (or any one of Schemes 1 to 5), wherein the maximum number of rings of the zeolite constituting the zeolite membrane is 10 or less.

[0017] The above-mentioned objectives, as well as other objectives, features, solutions, and advantages, will become clear from the following detailed description of the invention with reference to the accompanying drawings. Attached Figure Description

[0018] Figure 1 This is a cross-sectional view of a separation membrane composite according to one embodiment.

[0019] Figure 2 This is a magnified cross-sectional view showing a portion of the separation membrane complex.

[0020] Figure 3 This is a diagram showing the separation device.

[0021] Figure 4 This is a diagram illustrating the separation process of a mixture.

[0022] Figure 5 This is a diagram showing the manufacturing process of zeolite membrane composites.

[0023] Figure 6 This is a diagram showing the processing flow of zeolite membranes. Detailed Implementation

[0024] Figure 1 This is a cross-sectional view showing one embodiment of a zeolite membrane composite 1 treated by the zeolite membrane treatment method according to the present invention. Figure 2 This is an enlarged cross-sectional view showing a portion of the zeolite membrane composite 1. The zeolite membrane composite 1 includes a support 11 and a zeolite membrane 12. Figure 1 In the middle, the zeolite membrane 12 is drawn with thick lines. Figure 2 In the diagram, parallel oblique lines are marked on the zeolite membrane 12 to depict its thickness as thicker than it actually is.

[0025] The support 11 is a porous component that allows gas and liquid to pass through. Figure 1 In the example shown, the support 11 is a one-piece, integrally connected, generally cylindrical component. Multiple through holes 111 extending along the length direction are provided in the support 11. That is, the support 11 is a so-called integral component. The shape of the support 11 is, for example, generally cylindrical. The cross-section of each through hole 111 (i.e., compartment) perpendicular to the length direction is, for example, generally circular. Figure 1 In the diagram, the diameter of the through hole 111 is depicted as larger than it actually is, and the number of through holes 111 is depicted as fewer than it actually is.

[0026] The length of the support 11 (i.e., Figure 1The length (in the left-right direction) of the support 11 is, for example, 10cm to 200cm. The outer diameter of the support 11 is, for example, 0.5cm to 30cm. The distance between the central axes of adjacent through holes 111 is, for example, 0.3mm to 10mm. The surface roughness (Ra) of the support 11 is, for example, 0.1μm to 5.0μm, preferably 0.2μm to 2.0μm. It should be noted that the shape of the support 11 can be, for example, honeycomb, flat, tubular, cylindrical, prismatic, or polygonal. When the shape of the support 11 is tubular or cylindrical, the thickness of the support 11 is, for example, 0.1mm to 10mm.

[0027] The material of the support 11 only needs to be chemically stable during the process of forming the zeolite film 12 on its surface, and various substances (such as ceramics or metals) can be used. In this embodiment, the support 11 is formed using a ceramic sintered body. Examples of ceramic sintered bodies selected as the material for the support 11 include: alumina, silicon dioxide, andalusite, zirconium oxide, titanium dioxide, yttrium oxide, silicon nitride, and silicon carbide. In this embodiment, the support 11 includes at least one of alumina, silicon dioxide, and andalusite.

[0028] The support 11 may contain an inorganic binder. As an inorganic binder, at least one of the following can be used: titanium dioxide, andalusite, easily sinterable alumina, silica, glass frit, clay minerals, and easily sinterable cordierite.

[0029] The average pore size of the support 11 is, for example, 0.01 μm to 70 μm, preferably 0.05 μm to 25 μm. The average pore size of the support 11 near the surface to which the zeolite film 12 is to be formed is 0.01 μm to 1 μm, preferably 0.05 μm to 0.5 μm. For example, the average pore size can be measured using a mercury porosimeter, a pore size distribution measuring device, or a nanoscale pore size distribution measuring device. Regarding the overall pore size distribution of the support 11, including the surface and interior, D5 is, for example, 0.01 μm to 50 μm, D50 is, for example, 0.05 μm to 70 μm, and D95 ​​is, for example, 0.1 μm to 2000 μm. The porosity of the support 11 near the surface to which the zeolite film 12 is to be formed is, for example, 20% to 60%.

[0030] The support 11 may be a multilayer structure formed by stacking multiple layers with different average pore sizes in the thickness direction. The average pore size and sintered particle size of the surface layer, including the surface to which the zeolite film 12 is to be formed, are smaller than the average pore size and sintered particle size of the layers other than the surface layer. The average pore size of the surface layer of the support 11 is, for example, 0.01 μm to 1 μm, preferably 0.05 μm to 0.5 μm. When the support 11 has a multilayer structure, the materials of each layer can be the materials described above. The materials of the multiple layers forming the multilayer structure may be the same or different.

[0031] The zeolite membrane 12 is a generally cylindrical thin film disposed on the inner surface of the through-hole 111 of the support 11, covering approximately the entire inner surface. The zeolite membrane 12 is a dense porous membrane with micropores. A zeolite membrane is defined as at least as a membrane formed by zeolite on the surface of the support 11 or similar material, excluding membranes that merely disperse zeolite particles within an organic membrane. The zeolite membrane can be used as a separation membrane to separate specific substances from a mixture. In the zeolite membrane, other substances are less permeable than the specific substance. In other words, the permeation rate of the other substances in the zeolite membrane is lower than that of the specific substance. It should be noted that the zeolite membrane may include two or more types of zeolite with different structures and compositions.

[0032] The thickness of the zeolite membrane 12 is, for example, 0.05 μm to 30 μm, preferably 0.1 μm to 20 μm, and more preferably 0.5 μm to 10 μm. If the zeolite membrane 12 is thickened, the separation performance is improved. If the zeolite membrane 12 is thinned, the permeation rate increases. The surface roughness (Ra) of the zeolite membrane 12 is, for example, 5 μm or less, preferably 2 μm or less, more preferably 1 μm or less, and even more preferably 0.5 μm or less.

[0033] The pore size of the zeolite crystals contained in the zeolite membrane 12 (hereinafter also referred to as the "pore size of the zeolite membrane 12") is 0.2 nm or more and 0.8 nm or less, more preferably 0.25 nm or more and 0.7 nm or less, and even more preferably 0.28 nm or more and 0.45 nm or less. When the pore size of the zeolite membrane 12 is less than 0.2 nm, the amount of gas permeating through the zeolite membrane 12 may sometimes be less. When the pore size of the zeolite membrane 12 is greater than 0.8 nm, the selectivity of the zeolite membrane 12 for the gas may sometimes be insufficient. The pore size of the zeolite membrane 12 refers to the diameter (i.e., the minor axis) of the pores in the zeolite crystals constituting the zeolite membrane 12 in a direction approximately perpendicular to the maximum diameter of the pores (i.e., the maximum distance between oxygen atoms, i.e., the major axis). The pore size of the zeolite membrane 12 is smaller than the average pore size at the surface of the support 11 on which the zeolite membrane 12 is disposed.

[0034] When the maximum number of rings in the zeolite constituting the zeolite film 12 is n, the short axis of the n-membered ring pores is set as the pore diameter of the zeolite film 12. Furthermore, when the zeolite has multiple n-membered ring pores of equal size, the short axis of the n-membered ring pore with the largest short axis is set as the pore diameter of the zeolite film 12. It should be noted that an n-membered ring refers to a portion where the number of oxygen atoms constituting the framework forming the pores is n, and each oxygen atom bonds with T atoms (described later) to form a ring structure. Additionally, an n-membered ring refers to a ring that forms a through-hole (channel), excluding rings that do not form through-holes. An n-membered ring pore refers to a pore formed using n-membered rings. From the viewpoint of improving selectivity, the maximum number of rings in the zeolite film 12 is preferably 10 or less (e.g., 10, 8, or 6).

[0035] The pore size of the zeolite membrane 12 is uniquely determined by the skeletal structure of the zeolite and can be solved using the values ​​published in the "Database of Zeolite Structures" of the International Zeolite Society [online], URL: http: / / www.iza-structure.org / databases / >.

[0036] The type of zeolite constituting the zeolite film 12 is not particularly limited, and may include AEI, AEN, AFN, AFV, AFX, BEA, CHA, DDR, ERI, ETL, FAU (X and Y types), GIS, IHW, LEV, LTA, LTJ, MEL, MFI, MOR, MTN, PAU, RHO, SOD, and SAT types. Preferably, the zeolite constituting the zeolite film 12 is CHA, DDR, LTA, MFI, or MTN type zeolite.

[0037] In the zeolite constituting the zeolite film 12, the T atoms (i.e., the atoms located at the center of the oxygen tetrahedron (TO4) constituting the zeolite) include, for example, aluminum (Al). The zeolite constituting the zeolite film 12 can be a zeolite with only silicon (Si) as the T atom, or a zeolite with both Si and Al as the T atoms, an AlPO-type zeolite with Al and phosphorus (P) as the T atoms, a SAPO-type zeolite with Si, Al, and P as the T atoms, a MAPSO-type zeolite with magnesium (Mg), Si, Al, and P as the T atoms, or a ZnAPSO-type zeolite with zinc (Zn), Si, Al, and P as the T atoms, etc. A portion of the T atoms can be replaced by other elements.

[0038] The zeolite membrane 12, for example, contains Si. The zeolite membrane 12 may contain any two or more of Si, Al, and P. The zeolite membrane 12 may contain an alkali metal, such as sodium (Na) or potassium (K). When the zeolite membrane 12 contains both Si and Al atoms, the Si / Al ratio in the zeolite membrane 12 is, for example, 1 or more and 100,000 or less. The Si / Al ratio is the molar ratio of Si to Al elements contained in the zeolite membrane 12. This Si / Al ratio is preferably 5 or more, more preferably 20 or more, and even more preferably 100 or more; the higher the ratio, the better. The Si / Al ratio in the zeolite membrane 12 can be adjusted by adjusting the proportions of the Si source and Al source in the raw material solution, as described later.

[0039] Next, refer to Figure 3 and Figure 4 The separation of mixed substances using zeolite membrane complex 1 is explained. Figure 3 This is a diagram showing the separation device 2. Figure 4 This is a diagram illustrating the process of separating mixed substances based on separation device 2.

[0040] In the separation device 2, a mixture containing multiple fluids (i.e., gas or liquid) is supplied to the zeolite membrane composite 1, causing highly permeable substances in the mixture to permeate through the zeolite membrane composite 1, thereby separating them from the mixture. The separation in the separation device 2 can be performed, for example, to extract highly permeable substances (hereinafter also referred to as "highly permeable substances") from the mixture, or to concentrate substances with low permeability (hereinafter also referred to as "lowly permeable substances").

[0041] The mixture (i.e., the mixed fluid) can be a mixture of gases containing multiple gases, a mixture of liquids containing multiple liquids, or a gas-liquid two-phase fluid containing both gases and liquids.

[0042] The mixture includes, for example, one or more of the following: hydrogen (H2), helium (He), nitrogen (N2), oxygen (O2), water (H2O), water vapor (H2O), carbon monoxide (CO), carbon dioxide (CO2), nitrogen oxides, ammonia (NH3), sulfur oxides, hydrogen sulfide (H2S), sulfur fluoride, mercury (Hg), arsine (AsH3), hydrogen cyanide (HCN), carbonyl sulfide (COS), C1-C8 hydrocarbons, organic acids, alcohols, thiols, esters, ethers, ketones, and aldehydes. The highly permeable substances mentioned above include, for example, one or more of the following: H2, He, N2, O2, H2O, CO2, NH3, and H2S.

[0043] Nitrogen oxides refer to compounds of nitrogen and oxygen. Examples of nitrogen oxides include nitric oxide (NO), nitrogen dioxide (NO2), nitrous oxide (also known as dinitrogen monoxide) (N2O), dinitrogen trioxide (N2O3), dinitrogen tetroxide (N2O4), and dinitrogen pentoxide (N2O5), all collectively referred to as NO. X (NOx) gas.

[0044] Sulfur oxides are compounds of sulfur and oxygen. Examples of sulfur oxides include sulfur dioxide (SO2) and sulfur trioxide (SO3), collectively referred to as SO42-SO ... X (Sox) gas.

[0045] Sulfur fluoride refers to compounds of fluorine and sulfur. Examples of sulfur fluoride mentioned above include disulfur difluoride (F-S-S-F, S=SF2), sulfur difluoride (SF2), sulfur tetrafluoride (SF4), sulfur hexafluoride (SF6), or disulfur decafluoride (S2F). 10 )wait.

[0046] Hydrocarbons with C1 to C8 carbon atoms are defined as hydrocarbons with one or more but fewer than eight carbon atoms. Hydrocarbons with C3 to C8 carbon atoms can be any of the following: straight-chain compounds, side-chain compounds, and cyclic compounds. Additionally, hydrocarbons with C2 to C8 carbon atoms can be any of the following: saturated hydrocarbons (i.e., hydrocarbons without double or triple bonds in the molecule) and unsaturated hydrocarbons (i.e., hydrocarbons with double and / or triple bonds in the molecule). Examples of hydrocarbons with C1 to C4 carbon atoms include methane (CH4), ethane (C2H6), ethylene (C2H4), propane (C3H8), propylene (C3H6), n-butane (CH3(CH2)2CH3), isobutane (CH(CH3)3), 1-butene (CH2=CHCH2CH3), 2-butene (CH3CH=CHCH3), or isobutene (CH2=C(CH3)2).

[0047] The organic acids mentioned above are carboxylic acids or sulfonic acids, etc. Examples of carboxylic acids include formic acid (CH2O2), acetic acid (C2H4O2), oxalic acid (C2H2O4), acrylic acid (C3H4O2), or benzoic acid (C6H5COOH), etc. Examples of sulfonic acids include ethanesulfonic acid (C2H6O3S), etc. These organic acids can be chain compounds or cyclic compounds.

[0048] The alcohols mentioned above include, for example, methanol (CH3OH), ethanol (C2H5OH), isopropanol (2-propanol) (CH3CH(OH)CH3), ethylene glycol (CH2(OH)CH2(OH)) or butanol (C4H9OH), etc.

[0049] Thiols are organic compounds with hydrogenated sulfur (SH) at their terminals, also known as Thiol or Thioalcohol. Examples of thiols include methanethiol (CH3SH), ethanethiol (C2H5SH), and 1-propanethiol (C3H7SH).

[0050] The esters mentioned above are, for example, formate esters or acetate esters.

[0051] The ethers mentioned above are, for example, dimethyl ether ((CH3)2O), methyl ethyl ether (C2H5OCH3), or diethyl ether ((C2H5)2O), etc.

[0052] The ketones mentioned above include acetone ((CH3)2CO), methyl ethyl ketone (C2H5COCH3), or diethyl ketone ((C2H5)2CO), etc.

[0053] The aldehydes mentioned above include acetaldehyde (CH3CHO), propionaldehyde (C2H5CHO), or butylaldehyde (C3H7CHO).

[0054] In the following description, we will take as an example a mixture of multiple gases that is separated by the separation device 2.

[0055] The separation device 2 includes: a zeolite membrane composite 1, a sealing part 21, a housing 22, two sealing components 23, a supply part 26, a first recovery part 27, and a second recovery part 28. The zeolite membrane composite 1, the sealing part 21, and the sealing components 23 are housed within the housing 22. The supply part 26, the first recovery part 27, and the second recovery part 28 are disposed outside the housing 22 and connected to the housing 22.

[0056] The sealing part 21 is: installed in the longitudinal direction of the support 11 (i.e., Figure 3 The sealing portion 21 is a component that seals the two ends of the support body 11 in the left-right direction and covers and seals the two end faces of the support body 11 in the longitudinal direction and the outer surfaces near the two end faces. The sealing portion 21 prevents gas and liquid from flowing in and out relative to the two end faces of the support body 11. The sealing portion 21 is, for example, a plate-shaped or film-shaped component made of glass or resin. The material and shape of the sealing portion 21 can be appropriately changed. It should be noted that the sealing portion 21 is provided with multiple openings that coincide with the multiple through holes 111 of the support body 11 in the longitudinal direction. Therefore, the two ends of each through hole 111 of the support body 11 in the longitudinal direction are not covered by the sealing portion 21. Therefore, gas and liquid can flow in and out from the two ends through the through holes 111.

[0057] The shape of the outer shell 22 is not particularly limited; for example, it may be a generally cylindrical cylindrical component. The outer shell 22 is formed of, for example, stainless steel or carbon steel. The length direction of the outer shell 22 is approximately parallel to the length direction of the zeolite membrane composite 1. At one end of the length direction of the outer shell 22 (i.e., Figure 3 A supply port 221 is provided at the left end of the housing 22, and a first discharge port 222 is provided at the other end. A second discharge port 223 is provided on the side of the housing 22. A supply section 26 is connected to the supply port 221. A first recovery section 27 is connected to the first discharge port 222. A second recovery section 28 is connected to the second discharge port 223. The internal space of the housing 22 is a sealed space isolated from the space surrounding the housing 22.

[0058] Two sealing components 23 are arranged circumferentially between the outer surface of the zeolite membrane composite 1 and the inner surface of the outer shell 22 near both ends along the length of the zeolite membrane composite 1. Each sealing component 23 is a generally annular component formed of a gas- and liquid-impermeable material. For example, the sealing component 23 is an O-ring formed of a flexible resin. The sealing components 23 are tightly fitted circumferentially to the outer surface of the zeolite membrane composite 1 and the inner surface of the outer shell 22. Figure 3 In the example shown, the sealing component 23 is sealed to the outer side of the sealing part 21 and indirectly sealed to the outer side of the zeolite membrane composite 1 by sandwiching the sealing part 21. The sealing component 23 is sealed between itself and the outer side of the zeolite membrane composite 1 and between itself and the inner side of the outer shell 22, so that gas and liquid can hardly or completely pass through.

[0059] The supply unit 26 supplies the mixed gas into the internal space of the outer casing 22 via the supply port 221. The supply unit 26 may include, for example, a pressure conveying mechanism such as a blower or pump that pressurizes the mixed gas toward the outer casing 22. This pressure conveying mechanism may include, for example, a temperature regulating unit and a pressure regulating unit that respectively regulate the temperature and pressure of the mixed gas supplied to the outer casing 22. The first recovery unit 27 and the second recovery unit 28 may include, for example, a storage container for storing the gas discharged from the outer casing 22 or a blower or pump for transferring the gas.

[0060] When separating mixed gases, firstly, prepare zeolite membrane composite 1 ( Figure 4 (Step S11). Specifically, the zeolite membrane composite 1 is installed inside the housing 22. Next, using the supply unit 26, a mixed gas containing multiple gases with different permeabilities to the zeolite membrane 12 is supplied to the inside of the housing 22 as shown by arrow 251.

[0061] The pressure of the mixed gas supplied from the supply section 26 to the interior of the outer casing 22 (i.e., the supply-side pressure, which is the gas pressure on the primary side of the zeolite membrane 12) is, for example, 0.1 MPaG to 20.0 MPaG. The temperature of the mixed gas supplied from the supply section 26 is, for example, 10°C to 250°C.

[0062] The mixed gas supplied from the supply unit 26 to the outer casing 22 is introduced from the left end of the zeolite membrane composite 1 in the figure into each through hole 111 of the support 11 (i.e., the inner side of the generally cylindrical zeolite membrane 12). The highly permeable gas in the mixed gas, i.e., the high-permeability gas, permeates through the zeolite membrane 12 and the support 11 provided on the inner side of each through hole 111 and is discharged from the outer side of the support 11. Accordingly, the highly permeable gas is separated from the low-permeability gas in the mixed gas (step S12).

[0063] The gas discharged from the outer surface of the support 11 (hereinafter referred to as "permeable gas") is guided to the second recovery unit 28 via the second outlet 223 as shown by arrow 253, and recovered by the second recovery unit 28. The pressure of the gas recovered by the second recovery unit 28 (i.e., the permeable side pressure, which is the gas pressure on the secondary side of the zeolite membrane 12) is, for example, 0.0 MPaG. In other words, the difference between the supply side pressure and the permeable side pressure is, for example, 0.1 MPa to 20.0 MPa. In addition to the high permeability gas described above, the permeable gas may also contain low permeability gas that has already permeated through the zeolite membrane 12.

[0064] In addition, gases in the mixed gas other than those that have permeated through the zeolite membrane 12 and the support 11 (hereinafter referred to as "non-permeable gases") pass through the through holes 111 of the support 11 from left to right in the figure, as shown by arrow 252, and are recovered by the first recovery unit 27 via the first outlet 222. The pressure of the gas recovered by the first recovery unit 27 is, for example, approximately the same as the supply side pressure. In addition to the low-permeability gases mentioned above, the non-permeable gases may also include high-permeability gases that have not permeated through the zeolite membrane 12. The non-permeable gases recovered by the first recovery unit 27 can, for example, be recycled to the supply unit 26 and supplied back into the housing 22.

[0065] The zeolite membrane composite 1 described above is manufactured as follows. First, the support 11 is immersed in a solution containing dispersed seed crystals, causing the seed crystals to adhere to the support 11. Figure 5 (Step S21). The seed crystal is, for example, powder of zeolite produced by hydrothermal synthesis or a substance obtained by pulverizing the powder. It should be noted that the seed crystal can also be attached to the support 11 by methods other than those described above.

[0066] Next, the support 11 with seed crystals attached is immersed in the raw material solution for hydrothermal synthesis (step S22). Thereby, zeolite grows using the seed crystals as nuclei, forming a zeolite film 12 on the support 11. The raw material solution is prepared by dissolving or dispersing raw materials such as Si source and structure-directing agent (hereinafter also referred to as "SDA") in a solvent (e.g., water). The hydrothermal synthesis temperature is, for example, 110°C to 200°C, and the hydrothermal synthesis time is, for example, 5 hours to 200 hours.

[0067] After hydrothermal synthesis, the support 11 and zeolite membrane 12 are cleaned and dried, and then heat treatment is performed on the support 11 and zeolite membrane 12 under an oxidizing gas atmosphere (step S23). This heat treatment removes SDA and impurities from the zeolite membrane 12 by combustion. As a result, a zeolite membrane composite 1 with interconnected micropores is obtained. The aforementioned oxidizing gas atmosphere is an atmosphere containing oxygen, such as atmospheric air. The temperature during the heat treatment is, for example, 200°C or higher and 800°C or lower, preferably 300°C or higher and 600°C or lower, more preferably 350°C or higher and 500°C or lower. The heat treatment time is, for example, 10 to 200 hours.

[0068] The manufactured zeolite membrane composite 1 is stored, for example, in the atmosphere before actual use (e.g., shipment, installation in a separation device, etc.). In the freshly manufactured zeolite membrane composite 1, a relatively large amount of atmospheric water molecules are adsorbed onto the zeolite membrane 12, which is set to a relatively high temperature during the aforementioned heat treatment. These water molecules are adsorbed onto the surface of the zeolite membrane 12 opposite to the support 11 (i.e., the outer surface) and the surface within the pores of the zeolite membrane 12 (i.e., the inner surface). Furthermore, in the zeolite membrane composite 1 stored directly after heat treatment, a relatively large amount of water molecules are also adsorbed toward the zeolite membrane 12.

[0069] When a large number of water molecules are adsorbed onto the zeolite membrane 12, it is assumed that on the surface of the zeolite membrane 12 (i.e., the aforementioned outer and inner surfaces), water molecules are adsorbed in a multilayered manner in a direction approximately perpendicular to the surface (i.e., a multilayer adsorption state). Furthermore, phenomena such as some water molecules in the multilayer adsorption state detaching from the zeolite membrane 12, or atmospheric water molecules being further adsorbed onto water molecules in the multilayer adsorption state, as described above, may cause deviations in the permeation performance (e.g., separation performance, permeation rate) of the zeolite membrane 12 in multiple zeolite membrane composites 1 that are directly stored after heat treatment.

[0070] Therefore, in order to suppress the aforementioned deviation in the permeation performance of the zeolite membrane 12 in this invention, the following processing method involved in this invention is used (see [reference]). Figure 6The zeolite membrane 12 is then subjected to treatment (hereinafter also referred to as "post-treatment"). In this treatment method, firstly, preparation is made using the above-described step S23 (refer to...). Figure 5 The zeolite membrane 12 has undergone heat treatment (step S31). Preferably, the zeolite membrane composite 1 is prepared after the heat treatment has ended and the temperature has just cooled to room temperature (e.g., 25°C).

[0071] Next, a water-containing gas with a volumetric moisture content (i.e., water content on a volume basis) of 4000 ppmv or more and 65000 ppmv or less is brought into contact with the zeolite membrane 12 of the zeolite membrane composite 1, thereby causing water molecules to be adsorbed onto the zeolite membrane 12 (step S32). The volumetric moisture content of the water-containing gas is preferably 5500 ppmv or more, more preferably 7500 ppmv or more. Furthermore, the volumetric moisture content of the water-containing gas is preferably 40000 ppmv or less, more preferably 20000 ppmv or less. It is assumed that, at the end of the water molecule adsorption treatment in step S32, water molecules are adsorbed onto the zeolite membrane 12 in a multilayer adsorption state.

[0072] The aforementioned moisture-containing gas is, for example, atmospheric air. In step S32, for example, atmospheric air with a relative humidity of 25% or higher and 80% or lower is brought into contact with the zeolite membrane 12, thereby causing water molecules to be adsorbed onto the zeolite membrane 12. This contact between the atmospheric air and the zeolite membrane 12 is, for example, carried out by exposing the zeolite membrane composite 1 to the atmospheric air. The contact time between the atmospheric air and the zeolite membrane 12 is, for example, 1 hour or more. This contact time is, for example, 72 hours or less, preferably 48 hours or less, and more preferably 24 hours or less. By setting this contact time to 1 hour or more, the amount of water molecules required for the post-treatment is ideally adsorbed onto the zeolite membrane 12. In addition, by setting this contact time to 72 hours or less, an excess of water molecules adsorbed onto the zeolite membrane 12 can be suppressed. Furthermore, the time required for step S32 can also be prevented from becoming too long. Step S32 is carried out, for example, in an environment at atmospheric pressure and a temperature of 15°C or higher and 40°C or lower.

[0073] In step S32, the atmosphere used as the aforementioned moisture-containing gas also includes a gas that is substantially the same as the atmosphere in its natural state, with trace amounts of a substance added. It should be noted that gases other than the atmosphere can be used as the moisture-containing gas.

[0074] After step S32 is completed, a portion of the water molecules adsorbed on the zeolite membrane 12 are removed (step S33). In other words, in step S33, only a portion of the water molecules adsorbed on the zeolite membrane 12 are removed. Specifically, for example, water molecules that are adsorbed on the zeolite membrane 12 in a multilayer adsorption state but are not in direct contact with the zeolite membrane 12 (i.e., water molecules that are layered and adsorbed on top of water molecules directly adsorbed on the zeolite membrane 12) detach from the zeolite membrane 12 and become non-adsorbed.

[0075] At the end of the dehydration process in step S33, it is assumed that the water molecules on the surface of the zeolite membrane 12 (i.e., the aforementioned outer and inner surfaces) are in a monolayer adsorption state. A monolayer adsorption state refers to a state where water molecules on the surface of the zeolite membrane 12 are not substantially stacked with other water molecules but adsorbed onto the zeolite membrane 12 as a single layer. The monolayer adsorption state is more stable than the multilayer adsorption state described above; therefore, the detachment of water molecules adsorbed on the zeolite membrane 12 is suppressed compared to the multilayer adsorption state. Furthermore, on the surface of the zeolite membrane 12, the water molecules in the monolayer adsorption state are adsorbed at each adsorption site; therefore, there are essentially no new adsorption sites for water molecules to adsorb. Thus, the adsorption of new water molecules toward the zeolite membrane 12 is suppressed.

[0076] The partial removal of water molecules in step S33 can be achieved by a process of housing the zeolite membrane composite 1 together with the moisture adsorbent material in a container (hereinafter also referred to as "adsorbent material treatment"). This container is preferably a sealed container. For example, a container obtained by heat-sealing (i.e., heat-sealing) the outer periphery of two overlapping sheet-like components approximately around their circumference can be used. The zeolite membrane composite 1 and a moisture adsorbent material such as silica gel are housed together in a sealed space within this sheet-like sealed container. This sealed space is filled with an inactive gas such as nitrogen or argon (Ar) or atmospheric air.

[0077] The two sheet-like components described above are, for example, laminated sheets with a three-layer structure. The innermost layer of each sheet-like component (i.e., the layer on the side with the most enclosed space) is formed, for example, using a synthetic resin. Examples of synthetic resins that can be used include nylon (NY, polyamide (PA)), polyethylene (PE), polypropylene (PP), polyethylene terephthalate (PET), polyvinyl chloride (PVC), polyvinylidene chloride (PVDC), polyvinyl alcohol (PVA), polycarbonate (PC), polystyrene (PS), polyacrylonitrile (PAN), ethylene-vinyl acetate copolymer (EVA), ethylene-vinyl alcohol copolymer (EVOH), ethylene-methacrylic acid copolymer (EMAA), polyethylene naphthalate (PEN), polyester, cellophane, imide, and polymers thereof.

[0078] The outermost layer (i.e., the layer in direct contact with the external atmosphere) of each of the aforementioned sheet-like components is formed, for example, using a synthetic resin. The same resin used for the innermost layer of the aforementioned sheet-like components can also be used as the synthetic resin.

[0079] The intermediate layer between the innermost and outermost layers of the aforementioned sheet-like components is formed, for example, by vapor-depositing a metallic or ceramic material onto the outer surface of the innermost layer. Examples of metallic materials used include aluminum (Al), chromium (Cr), zinc (Zn), gold (Au), silver (Ag), platinum (Pt), and nickel (Ni). Examples of ceramic materials used include alumina and silicon dioxide. The vapor deposition of the metallic or ceramic material is performed, for example, using plasma CVD (Chemical Vapor Deposition) or thermal CVD. This intermediate layer improves the airtightness of the sealed container and blocks external light.

[0080] The thickness of the innermost layer of each sheet-like component is, for example, 5 μm to 500 μm. The thickness of the middle layer of each sheet-like component is, for example, 10 nm to 100 nm. The thickness of the outermost layer of each sheet-like component is, for example, 5 μm to 30 μm.

[0081] The partial removal of water molecules in step S33 can be achieved by depressurization of the zeolite membrane 12. In this depressurization process, for example, the zeolite membrane composite 1 is placed in a sealed space inside the aforementioned sealed container or vacuum chamber and maintained under a vacuum atmosphere for at least 3 hours and at least 240 hours. The maintenance time of the zeolite membrane composite 1 under a vacuum atmosphere is preferably at least 6 hours and at least 72 hours, more preferably at least 12 hours and at least 24 hours. The pressure of the vacuum atmosphere in this depressurization process is, for example, 10... 4 Pa or less, preferably 10 Pa 2 Pa or less, more preferably 10 Pa -1 Below Pa.

[0082] The partial removal of water molecules in step S33 can be achieved by replacing the atmosphere surrounding the zeolite membrane 12 with a dry gas having a lower water volume fraction than the moisture-containing gas used in step S32 (hereinafter also referred to as "gas replacement treatment"). For example, the zeolite membrane composite 1 is housed in a sealed space within the aforementioned sealed container or a sealed space within the outer shell 22 of the aforementioned separation device 2, and the atmosphere of this sealed space is replaced with a dry gas, thereby partially removing the water molecules adsorbed on the zeolite membrane 12. For example, inert gases such as nitrogen or argon, or dry air with a dew point below -20°C at atmospheric pressure, can be used as the dry gas.

[0083] The partial removal of water molecules in step S33 can be achieved by blowing the aforementioned dry gas onto the zeolite membrane 12 (hereinafter also referred to as "gas blowing treatment"). For example, the zeolite membrane composite 1 is housed in the housing 22 of the separation device 2, and dry gas is supplied into the housing 22 from the supply unit 26, thereby blowing the dry gas onto the zeolite membrane 12 to partially remove water molecules adsorbed on the zeolite membrane 12.

[0084] The partial removal of water molecules in step S33 is achieved by performing any one or more of the four treatments described above (i.e., adsorbent material treatment, depressurization treatment, gas replacement treatment, and gas blowing treatment). It should be noted that the partial removal of water molecules in step S33 can be achieved by using other treatments different from the four treatments described above, or by combining such other treatments with any one or more of the four treatments described above.

[0085] By performing the post-processing described above (steps S31 to S33), the detachment of water molecules from the zeolite membrane 12 and further adsorption onto the zeolite membrane 12 can be suppressed. As a result, for example, when multiple zeolite membrane composites 1 prepared under the same conditions are stored in the atmosphere, deviations in the permeation performance (e.g., separation performance, permeation rate) of the zeolite membrane 12 caused by the adsorption and detachment of water molecules onto the zeolite membrane 12 can be suppressed. Furthermore, by changing the storage period of the same zeolite membrane composite, deviations in the permeation performance of the zeolite membrane 12 can be suppressed in a substantially similar manner.

[0086] It should be noted that in the above-described post-treatment of the zeolite membrane composite 1, if there is excessive adsorption of water molecules onto the zeolite membrane 12 in step S32, and the partial removal of water molecules in step S33 is not ideally performed, the permeation rate of the zeolite membrane 12 may decrease. On the other hand, if the adsorption of water molecules onto the zeolite membrane 12 in step S32 is insufficient, water molecules may be re-adsorbed onto the zeolite membrane 12 during evaluation of the permeation performance of the zeolite membrane composite 1 after step S33, and the permeation performance of the zeolite membrane 12 may be unstable. Furthermore, if there is excessive removal of water molecules (i.e., dehydration) in step S33, water molecules may also be re-adsorbed onto the zeolite membrane 12 during evaluation of the permeation performance of the zeolite membrane composite 1, and the permeation performance of the zeolite membrane 12 may be unstable.

[0087] As explained above, the above-described zeolite membrane treatment method includes the following steps: preparing a heat-treated zeolite membrane 12 (step S31); after step S31, contacting a water-containing gas with a volume water content of 4000 ppmv or more and 65000 ppmv or less with the zeolite membrane 12, thereby causing water molecules to be adsorbed onto the zeolite membrane 12 (step S32); and after step S32, partially removing the water molecules adsorbed onto the zeolite membrane 12 (step S33).

[0088] In this way, by temporarily contacting the zeolite membrane 12 with a moisture-containing gas to specifically adsorb water molecules onto the zeolite membrane 12, and then removing the excess portion of the water molecules adsorbed onto the zeolite membrane 12, water molecules can exist in a monolayer adsorption state on the surface of the zeolite membrane 12 (i.e., the aforementioned outer and inner surfaces). As mentioned above, the monolayer adsorption state is more stable than the multilayer adsorption state. Furthermore, on the surface of the zeolite membrane 12, water molecules in the monolayer adsorption state are adsorbed at each adsorption site; therefore, there are essentially no new adsorption sites for water molecules to adsorb. Thus, in the zeolite membrane 12 treated using the above-described zeolite membrane treatment method (steps S31 to S33), the detachment of adsorbed water molecules is suppressed, and the adsorption of new water molecules is also suppressed. As a result, the permeation performance of the zeolite membrane 12 can be stabilized, and the zeolite membrane 12 can be stored in a state of stable permeation performance.

[0089] Preferably, in step S33, one or more of the following processes are performed: depressurization treatment of the zeolite membrane 12, replacement of the atmosphere surrounding the zeolite membrane 12 with a dry gas having a lower water volume fraction than the water-containing gas, blowing the dry gas onto the zeolite membrane 12, and storing the zeolite membrane 12 together with the water adsorption material in a container. This process partially removes the water molecules adsorbed on the zeolite membrane 12. Accordingly, the excess amount of water molecules adsorbed on the zeolite membrane 12 in step S32 can be ideally removed.

[0090] More preferably, in step S33, a depressurization treatment is performed on the zeolite membrane 12, in which the zeolite membrane 12 is held in a vacuum atmosphere for 3 hours or more and 240 hours or less. This allows for the further and more ideal removal of excess water molecules adsorbed on the zeolite membrane 12 in step S32. Specifically, by setting the holding time of the zeolite membrane composite 1 in a vacuum atmosphere to 3 hours or more, excess water molecules remaining on the surface of the zeolite membrane 12 can be suppressed. Furthermore, by setting this holding time to 240 hours or less, the excessive removal of water molecules adsorbed on the zeolite membrane 12 can be suppressed.

[0091] As described above, the moisture-containing gas is preferably atmospheric air. Accordingly, in step S32, water molecules can be ideally adsorbed onto the zeolite membrane 12. Furthermore, step S32 can be easily implemented. In addition, compared to the case where the moisture-containing gas is a gas other than atmospheric air, the cost required for preparing and using the moisture-containing gas can be reduced.

[0092] More preferably, in step S32, air with a relative humidity of 25% or higher and 80% or lower is brought into contact with the zeolite membrane 12 for 1 hour or more and 72 hours or less, thereby causing water molecules to be adsorbed onto the zeolite membrane 12. This allows for more ideal adsorption of water molecules onto the zeolite membrane 12. Specifically, by setting the relative humidity to 25% or higher, a sufficient amount of water molecules can be adsorbed onto the zeolite membrane 12. Furthermore, by setting the relative humidity to 80% or lower, excessive adsorption of water molecules onto the zeolite membrane 12 can be suppressed. By setting the contact time between the air and the zeolite membrane 12 to 1 hour or more, a sufficient amount of water molecules can be adsorbed onto the zeolite membrane 12. Furthermore, by setting the contact time between the air and the zeolite membrane 12 to 72 hours or less, excessive adsorption of water molecules onto the zeolite membrane 12 can be suppressed.

[0093] Preferably, the maximum number of rings in the zeolite constituting the zeolite membrane 12 is 10 or less. In such a zeolite membrane 12, since the average pore size is relatively small, the adsorption of water molecules on the surface of the pores has a relatively large impact on the permeation performance. As described above, according to the zeolite membrane treatment method shown in steps S31 to S33, the adsorption of water molecules on the zeolite membrane 12 can be controlled, and the permeation performance of the zeolite membrane 12 can be stabilized. Therefore, this treatment method is particularly suitable for treating the aforementioned zeolite membrane 12 where the adsorption of water molecules has a relatively large impact on the permeation performance.

[0094] Next, referring to Tables 1 and 2, the relationship between the post-treatment (steps S31 to S33) of the zeolite membrane 12 and the stabilization of its permeation performance will be explained.

[0095] Table 1

[0096]

[0097] Table 2

[0098]

[0099] In Examples 1-4 and Comparative Examples 1-10 in Tables 1 and 2, the stabilization of the permeation performance of the zeolite membrane 12 was evaluated using the coefficient of variation of the permeation rate of the highly permeable gas and the coefficient of variation of the separation ratio. Specifically, when the coefficient of variation of the permeation rate of the highly permeable gas is 0.15 or less and the coefficient of variation of the separation ratio is 0.15 or less, the permeation performance of the zeolite membrane 12 is considered to be stable. On the other hand, when the coefficient of variation of the permeation rate of the highly permeable gas is greater than 0.15 and / or the coefficient of variation of the separation ratio is greater than 0.15, the permeation performance of the zeolite membrane 12 is considered to have a large variation, and the stability of the permeation performance of the zeolite membrane 12 is insufficient.

[0100] The permeation rate of highly permeable gases is obtained by supplying a mixed gas to the zeolite membrane composite 1 in the separation device 2 described above, and measuring the permeation rate (permeability) of the highly permeable gas per unit membrane area and unit pressure difference permeating through the zeolite membrane 12. The coefficient of variation of the permeation rate of highly permeable gases (hereinafter also referred to as the "permeation rate variation coefficient") is obtained by dividing the standard deviation of the measured values ​​by the arithmetic mean of the measured values ​​after performing the measurement of the permeation rate five times. The separation ratio is obtained by dividing the permeation rate of highly permeable gases per unit membrane area and unit pressure difference permeable through the zeolite membrane 12 by the permeation rate of low permeable gases per unit membrane area and unit pressure difference permeable through the zeolite membrane 12 after supplying a mixed gas to the zeolite membrane composite 1 in the separation device 2. The coefficient of variation of the separation ratio (hereinafter also referred to as the "separation ratio variation coefficient") is obtained by dividing the standard deviation of the measured values ​​by the arithmetic mean of the measured values ​​after performing the measurement of the separation ratio five times. When evaluating the permeation performance of the zeolite membrane 12, the pressure and temperature of the mixed gas supplied from the supply section 26 of the separation device 2 were 0.3 MPaG and 25°C, respectively.

[0101] In Example 1, the zeolite constituting the zeolite membrane 12 is of the DDR type. In step S32, the water-containing gas in contact with the zeolite membrane 12 during the water molecule adsorption treatment is atmospheric air, with a volumetric water content, temperature, and relative humidity of 11680 ppmv, 20°C, and 50%, respectively. Furthermore, the contact time between the water-containing gas and the zeolite membrane 12 is 12 hours. The dehydration treatment in step S33 is performed using the aforementioned decompression treatment. The pressure during the decompression treatment, the holding time of the zeolite membrane composite 1 under decompression, and the holding temperature are 10... -1 Pa, 24 hours, and 22°C. The decompression treatment was carried out using the aforementioned sheet-like sealed container.

[0102] The permeation performance of zeolite membrane 12 was evaluated using a mixture of CO2 and CH4 gases. In this mixture, CO2 is a highly permeable gas, and CH4 is a low-permeability gas. The concentrations of CO2 and CH4 in the mixture were 50% by volume. The permeation rate variation coefficient was 0.02, and the separation ratio variation coefficient was 0.07. Therefore, the permeation performance of zeolite membrane 12 was considered stable, and the evaluation related to the stability of its permeation performance was "good".

[0103] In Example 2, the volumetric moisture content, temperature, and relative humidity of the water-containing gas in the water molecule adsorption treatment of step S32 were 4226 ppmv, 15°C, and 25%, respectively. Otherwise, it was the same as in Example 1. The permeation rate variation coefficient and the separation ratio variation coefficient were 0.08 and 0.13, respectively, and the evaluation related to the stability of the permeation performance of the zeolite membrane 12 was "good".

[0104] In Example 3, the volumetric moisture content, temperature, and relative humidity of the water-containing gas in the water molecule adsorption treatment of step S32 were 61920 ppmv, 40°C, and 80%, respectively. Otherwise, it was the same as in Example 1. The permeation rate variation coefficient and the separation ratio variation coefficient were 0.10 and 0.12, respectively, and the evaluation related to the stability of the permeation performance of the zeolite membrane 12 was "good".

[0105] In Example 4, the dehydration process in step S33 was performed by gas displacement, otherwise it was the same as in Example 1. The gas displacement process was carried out in the separation device 2 described above, and nitrogen was used as the drying gas. The permeation rate variation coefficient and the separation ratio variation coefficient were 0.04 and 0.09, respectively, and the evaluation related to the stability of the permeation performance of the zeolite membrane 12 was "good".

[0106] In Example 5, the dehydration process in step S33 was performed by gas blowing, otherwise it was the same as in Example 1. The gas blowing process was carried out using the separation device 2 described above, and dry air with a dew point of -20°C at atmospheric pressure was used as the drying gas. The permeation rate variation coefficient and the separation ratio variation coefficient were 0.03 and 0.10, respectively, and the evaluation related to the stability of the permeation performance of the zeolite membrane 12 was "good".

[0107] In Example 6, the dehydration process in step S33 was performed using an adsorbent material, otherwise it was the same as in Example 1. The adsorbent material treatment was carried out using the aforementioned sheet-like sealed container, and silica gel was used as the adsorbent material. The permeation rate variation coefficient and the separation ratio variation coefficient were 0.04 and 0.08, respectively, and the evaluation related to the stability of the permeation performance of the zeolite membrane 12 was "good".

[0108] In Example 7, the zeolite constituting the zeolite membrane 12 was of the MFI type, and the evaluation of the permeation performance of the zeolite membrane 12 was conducted using a mixture of N2 and SF6, otherwise identical to Example 1. In this mixture, N2 was a high-permeability gas, and SF6 was a low-permeability gas. The concentration of N2 in the mixture was 80% by volume, and the concentration of SF6 was 20% by volume. The permeation rate variation coefficient and the separation ratio variation coefficient were 0.04 and 0.13, respectively, and the evaluation related to the stability of the permeation performance of the zeolite membrane 12 was "good".

[0109] In Example 8, the zeolite constituting the zeolite membrane 12 was of the CHA type, otherwise it was the same as in Example 1. The permeation rate variation coefficient and the separation ratio variation coefficient were 0.05 and 0.09, respectively, and the evaluation related to the stability of the permeation performance of the zeolite membrane 12 was "good".

[0110] In Comparative Example 1, the water molecule adsorption treatment in step S32 and the dehydration treatment in step S33 were not performed; otherwise, it was the same as in Example 1. The permeation rate variation coefficient was 0.15, and the separation ratio variation coefficient was 0.50. In Comparative Example 1, the separation ratio variation coefficient was greater than 0.15, indicating a large deviation in the separation ratio. Therefore, the permeation performance of the zeolite membrane 12 was considered unstable, and the evaluation related to the stability of the permeation performance of the zeolite membrane 12 was "poor".

[0111] In Comparative Example 2, the dehydration treatment in step S33 was not performed; otherwise, it was the same as in Example 1. The permeation rate variation coefficient was 0.21, and the separation ratio variation coefficient was 0.23. In Comparative Example 2, the permeation rate variation coefficient was greater than 0.15, indicating a large deviation in permeation rate. Additionally, the separation ratio variation coefficient was greater than 0.15, indicating a large deviation in separation ratio. Therefore, the permeation performance of the zeolite membrane 12 was considered unstable, and the evaluation related to the stability of the permeation performance of the zeolite membrane 12 was "poor".

[0112] In Comparative Example 3, the volumetric moisture content and relative humidity of the water-containing gas in the water molecule adsorption treatment of step S32 were 3480 ppmv and 15%, respectively, otherwise the same as in Example 1. The permeation rate variation coefficient was 0.15, and the separation ratio variation coefficient was 0.25. In Comparative Example 3, the separation ratio variation coefficient was greater than 0.15, indicating a large deviation in the separation ratio. Therefore, the evaluation related to the stability of the permeation performance of the zeolite membrane 12 was "poor".

[0113] In Comparative Example 4, the volumetric moisture content, relative humidity, and temperature of the water-containing gas in step S32's water molecule adsorption treatment were 70-200 ppmv, 90%, and 40°C, respectively, otherwise the same as in Example 1. The permeation rate variation coefficient was 0.24, and the separation ratio variation coefficient was 0.27. In Comparative Example 4, the permeation rate variation coefficient and separation ratio variation coefficient were relatively large, and the deviations in permeation rate and separation ratio were relatively large. Therefore, the evaluation related to the stability of the permeation performance of the zeolite membrane 12 was "poor".

[0114] In Comparative Example 5, the water molecule adsorption treatment in step S32 was not performed; otherwise, it was the same as in Example 1. The permeation rate variation coefficient was 0.14, and the separation ratio variation coefficient was 0.23. In Comparative Example 5, the separation ratio variation coefficient was large, and the deviation of the separation ratio was large. Therefore, the evaluation related to the stability of the permeation performance of the zeolite membrane 12 was "poor".

[0115] In Comparative Example 6, the dehydration treatment in step S33 was performed using the same gas replacement treatment as in Example 4, except that it was the same as in Comparative Example 5. The permeation rate variation coefficient was 0.18, and the separation ratio variation coefficient was 0.23. In Comparative Example 6, the permeation rate variation coefficient and the separation ratio variation coefficient were relatively large, and the deviations in permeation rate and separation ratio were relatively large. Therefore, the evaluation related to the stability of the permeation performance of the zeolite membrane 12 was "poor".

[0116] In Comparative Example 7, the dehydration process in step S33 was performed using the same gas blowing process as in Example 5, except that it was the same as in Comparative Example 5. The permeation rate variation coefficient was 0.19, and the separation ratio variation coefficient was 0.39. In Comparative Example 7, the permeation rate variation coefficient and the separation ratio variation coefficient were relatively large, and the deviations in permeation rate and separation ratio were relatively large. Therefore, the evaluation related to the stability of the permeation performance of the zeolite membrane 12 was "poor".

[0117] In Comparative Example 8, the dehydration treatment in step S33 was performed using the same adsorbent material as in Example 6, and otherwise, it was the same as in Comparative Example 5. The permeation rate variation coefficient was 0.20, and the separation ratio variation coefficient was 0.40. In Comparative Example 8, the permeation rate variation coefficient and the separation ratio variation coefficient were relatively large, and the deviations in permeation rate and separation ratio were relatively large. Therefore, the evaluation related to the stability of the permeation performance of the zeolite membrane 12 was "poor".

[0118] In Comparative Example 9, the water molecule adsorption treatment in step S32 and the dehydration treatment in step S33 were not performed; otherwise, it was the same as in Example 7. The permeation rate variation coefficient was 0.22, and the separation ratio variation coefficient was 0.31. In Comparative Example 9, the permeation rate variation coefficient and the separation ratio variation coefficient were relatively large, and the deviations in permeation rate and separation ratio were relatively large. Therefore, the evaluation related to the stability of the permeation performance of the zeolite membrane 12 was "poor".

[0119] In Comparative Example 10, the water molecule adsorption treatment in step S32 and the dehydration treatment in step S33 were not performed; otherwise, it was the same as in Example 8. The permeation rate variation coefficient was 0.18, and the separation ratio variation coefficient was 0.42. In Comparative Example 10, the permeation rate variation coefficient and the separation ratio variation coefficient were relatively large, and the deviation of the permeation rate and separation ratio was relatively large. Therefore, the evaluation related to the stability of the permeation performance of the zeolite membrane 12 was "poor".

[0120] Comparing Example 1 with Comparative Examples 1, 2, and 5 above, it can be seen that by performing the water molecule adsorption treatment in step S32 and the dehydration treatment in step S33, the permeation rate variation coefficient and the separation ratio variation coefficient are reduced, and the permeation performance of the zeolite membrane 12 has been stabilized.

[0121] Comparing Example 1 with Comparative Examples 3 and 4, it can be seen that the deviation in the permeation performance of the zeolite membrane 12 increases when the volume moisture content of the water-containing gas in the water molecule adsorption treatment in step S32 is below 4000 ppmv and when the volume moisture content is 65000 ppmv. Therefore, by setting the volume moisture content to above 4000 ppmv and below 65000 ppmv, the permeation performance of the zeolite membrane 12 can be stabilized.

[0122] Various modifications can be made to the above-mentioned treatment method for zeolite membrane 12.

[0123] For example, the maximum number of rings in the zeolite constituting the zeolite membrane 12 can be greater than 10.

[0124] In the water molecule adsorption treatment of step S32, when the atmosphere is used as the moisture-containing gas, the relative humidity of the atmosphere can be less than 25% or greater than 80%. In addition, the contact time between the atmosphere and the zeolite membrane 12 can be less than 1 hour or longer than 72 hours.

[0125] In the dehydration process of step S33, when the zeolite membrane 12 is subjected to decompression treatment, the holding time of the zeolite membrane 12 under vacuum atmosphere can be less than 3 hours or longer than 240 hours.

[0126] When water molecules are in an adsorbed state at the surface of the zeolite membrane 12, the dehydration process in step S33 does not necessarily require a change from a multilayer adsorption state to a monolayer adsorption state. For example, by performing the dehydration process in step S33, the number of layers (i.e., layer thickness) of water molecules adsorbed on the surface of the zeolite membrane 12 can be reduced while maintaining the multilayer adsorption state. Alternatively, by performing the dehydration process in step S33, the adsorption state can be changed from a multilayer adsorption state to a monolayer adsorption state on a portion of the surface of the zeolite membrane 12, while maintaining the multilayer adsorption state on other portions of the surface of the zeolite membrane 12, thereby reducing the number of layers (i.e., layer thickness).

[0127] In Examples 1 to 4 described above, a mixture of CO2 and CH4 or a mixture of N2 and SF6 was used to evaluate the permeation performance of the zeolite membrane 12. However, as mentioned above, the mixture separated by the zeolite membrane 12 in the separation device 2 and the like can contain various components. For example, the mixture can be a mixture containing H2 as a highly permeable gas and N2 as a low-permeability gas as the main components. The mixture can also contain gases other than H2 and N2 (e.g., NH3 and / or H2O).

[0128] The zeolite membrane 12 can be a laminated membrane obtained by stacking multiple zeolite membranes formed from different types of zeolite in the thickness direction, or it can be a zeolite membrane that has undergone surface treatment. In addition, in the zeolite membrane composite 1, a membrane of a different type from the zeolite membrane (such as an inorganic membrane other than a zeolite membrane, like a silica membrane) can be provided on the zeolite membrane 12 (i.e., on the outer surface of the zeolite membrane 12 on the side opposite to the support 11).

[0129] The components in the above-described embodiments and their variations can be appropriately combined as long as they do not contradict each other.

[0130] Although the invention has been described in detail, the above description is exemplary and not limiting. Therefore, it can be said that numerous modifications and solutions can be adopted without departing from the scope of the invention.

[0131] Industrial availability

[0132] This invention can be used when processing zeolite membranes that can be used to separate various types of mixed gases.

[0133] Explanation of reference numerals in the attached figures

[0134] 12 Zeolite membrane

[0135] Steps S11~S12, S21~S23, S31~S33

Claims

1. A method for treating zeolite membranes, comprising the following steps: a) Prepare heat-treated zeolite membranes; b) After step a), a water-containing gas with a volume water content of 4000 ppmv or higher and 65000 ppmv or lower is brought into contact with the zeolite membrane, thereby causing water molecules to be adsorbed onto the zeolite membrane; and c) After step b), the water molecules adsorbed on the zeolite membrane are partially removed.

2. The method for treating zeolite membranes according to claim 1, wherein, In step c), water molecules adsorbed on the zeolite membrane are partially removed by performing one or more of the following treatments. The processing is as follows: Decompression treatment for the zeolite membrane, The treatment involves replacing the atmosphere surrounding the zeolite film with a dry gas having a lower moisture volume fraction than the moisture-containing gas. Treatment of the dry gas blown by the zeolite membrane, The process of storing the zeolite membrane together with the moisture-absorbing material in a container.

3. The method for treating zeolite membranes according to claim 2, wherein, In step c), a decompression treatment is performed on the zeolite membrane. In the decompression treatment, the zeolite membrane is kept in a vacuum atmosphere for more than 3 hours and less than 240 hours.

4. The method for treating zeolite membranes according to any one of claims 1 to 3, wherein, The moisture-containing gas is atmospheric air.

5. The method for treating zeolite membranes according to claim 4, wherein, In step b), the zeolite membrane is brought into contact with an atmosphere with a relative humidity of 25% or more and 80% or less for more than 1 hour and less than 72 hours, thereby causing water molecules to be adsorbed onto the zeolite membrane.

6. The method for treating zeolite membranes according to any one of claims 1 to 3, wherein, The maximum number of rings in the zeolite constituting the zeolite membrane is 10 or less.

Citation Information

Patent Citations

  • Method for producing porous support-zeolite membrane composite

    JP2013013884A

  • Production method of porous support-zeolite membrane composite

    JP2016159185A

  • Methods of synthesizing a polynucleotide array using photoactivated agents

    JP2024041921A